Padrões e processos macroevolutivos na origem e diversificação de vertebrados terrestres da Floresta Atlântica - Matheus de Toledo Moroti (2023)
The Atlantic Forest is one of the global hotspots of biodiversity due to the high number of endemic species under a high degree of threat. Several hypotheses have been proposed to explain the causes of high biodiversity in this biome, such as the refuge hypothesis. On the other hand, barriers to dispersal and allopatric speciation seem to be important in determining genetic diversity in some species. However, there is still no consensus on the relative importance of these processes or how they vary across space and among organisms with different dispersal abilities and thermal tolerance. Therefore, initiatives that integrate approaches from areas such as ecology, macroevolution, and phenotypic evolution can contribute to a better understanding of the key processes involved in the formation of the Atlantic Forest biota. The objective of this thesis was to identify the macroevolutionary processes involved in the origin and diversity of terrestrial vertebrates in the Atlantic Forest. The thesis is divided into two chapters: the first entitled "Productivity interacts with diversification rate in determining species richness and trait diversity of tetrapods in a global hotspot" and the second "The effects of climatic niche on the rate of body size evolution in terrestrial vertebrates". In the first chapter, we were interested in investigating which variables from equilibrium dynamics (topography, climate, and primary productivity) and non-equilibrium dynamics (diversification rate and assemblage age) explain species richness and functional diversity of the four clades of terrestrial vertebrates (anuran amphibians, squamata reptiles, birds and non-volant mammals) in the Atlantic Forest. We also investigated whether their spatial patterns are congruent among the groups. We found that species richness and functional diversity have the same predictors in vertebrate lineages but operate differently in space. The clade diversity was not affected by speciation time, while diversification rate had a strong positive influence on functional diversity and species richness. Our results emphasize the need to evaluate multiple taxa when testing alternative explanations for diversity patterns. In the second chapter, we were interested in testing whether the rate of body size evolution in terrestrial vertebrates is impacted by the climatic niche. We found that terrestrial vertebrates exhibit idiosyncratic patterns of phenotypic evolution over time, with some lineages accelerating and others decelerating their evolutionary rates. Additionally, we did not find a significant relationship between phenotypic evolution rates and the climatic niche. However, amplitude influences the variation in rates more than niche position. These results highlight the importance of selective pressures and specific characteristics of each group in phenotypic evolution. Furthermore, it is possible that different axes of the species' ecological niche impact the evolutionary rates of body size in terrestrial vertebrates. Together, these chapters provide a more complete view of the processes that shaped the Atlantic Forest biota, encompassing both macroecological and macroevolutionary aspects of terrestrial vertebrate communities. Our findings have implications for our understanding of the drivers of biodiversity and evolutionary changes in vertebrate phenotypic rates, as well as the factors that shape biodiversity patterns at regional scales.